2018
DOI: 10.1371/journal.pbio.2004920
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary novelty in gravity sensing through horizontal gene transfer and high-order protein assembly

Abstract: Horizontal gene transfer (HGT) can promote evolutionary adaptation by transforming a species’ relationship to the environment. In most well-understood cases of HGT, acquired and donor functions appear to remain closely related. Thus, the degree to which HGT can lead to evolutionary novelties remains unclear. Mucorales fungi sense gravity through the sedimentation of vacuolar protein crystals. Here, we identify the octahedral crystal matrix protein (OCTIN). Phylogenetic analysis strongly supports acquisition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Gravitropism in Phycomyces is apparently mediated by a differential flux of H + and Ca 2+ in the mycelium (Živanović, , , ; Göttig & Galland, ). However, statoliths in this fungus seem to have originated from a recent bacterial gene transfer (Nguyen et al ., ). In the absence of crystalline structures in other lineages, it has been proposed that nuclei themselves might act as statolith‐like structures in Agaricomycotina (Monzer, , ; Moore et al ., ; Kern, Mendgen & Hock, ).…”
Section: Cellular Complexitymentioning
confidence: 97%
“…Gravitropism in Phycomyces is apparently mediated by a differential flux of H + and Ca 2+ in the mycelium (Živanović, , , ; Göttig & Galland, ). However, statoliths in this fungus seem to have originated from a recent bacterial gene transfer (Nguyen et al ., ). In the absence of crystalline structures in other lineages, it has been proposed that nuclei themselves might act as statolith‐like structures in Agaricomycotina (Monzer, , ; Moore et al ., ; Kern, Mendgen & Hock, ).…”
Section: Cellular Complexitymentioning
confidence: 97%
“…in lichens and mycorrhizal species) that often involve prokaryotes have predisposed some lineages to higher rates of LGT [35,[78][79][80][81][82]. In fact, interdomain LGT has been implicated in important fungal innovations from gravity-sensing organs to pathogenic mechanisms and toxin-encoding genes [34,35,83,84]. In addition, some fungal species and genera seem to be especially prone to receiving LGTs, including the genera Aspergillus and Fusarium, for which genomic data are available [35,85] and in which we also observe frequently in putative LTG trees.…”
Section: Ltgs Unique To Non-photosynthetic Eukaryotesmentioning
confidence: 99%
“…Furthermore, all magnetoreceptive microorganisms identified to date are those coupling magnetoreception and geolocalization to navigation. But other biological systems showed that geolocalization may be used for a purpose other than navigation, as some immobile fungi that use gravity instead to sense verticality and direct the spread of spores [66]. Thus, beyond exploring the diversity of magnetotactic organisms, alternative protocols should be developed to isolate magnetoreceptive microorganisms that are not magnetotactic.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%